Pengaruh Social Media Content, E-Wom, Brand Awareness, Influencer Marketing terhadap Purchase Intention - Siti Latifah; Puspita Chairun Nisa; Jatmiko Jatmiko (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Marketing strategies for online shopping companies are heavily influenced by purchase intention, as it plays a crucial role in increasing company revenue. With the advancement of digital technology, social media has become a dominant platform for product promotion, potentially boosting purchase intention. This study aims to analyze the influence of social media content, e-WOM, brand awareness, and influencer marketing on purchase intention among TikTok app users. Data were collected through questionnaires from TikTok app users with the TikTok Shop feature using purposive sampling with the Structural Equation Model – Partial Least Squares (SEM-PLS) method. The study found that social media content and e-WOM influence purchase intention, while brand awareness and influencer marketing have no effect. However, influencer marketing does influence brand awareness. This study provides implications for companies using TikTok as a digital commerce platform to focus on marketing strategies to increase purchase intention through short, creatively edited product videos, creating review incentive programs for consumers, incorporating supporting elements into their products, such as competitive pricing and guaranteed product quality, and selecting influencers who align with their target market values through authentic video content. Further research suggests expanding the geographic scope of respondents, adding independent variables, and using other applications to increase purchase intention on the TikTok app.